Strategi Pemasaran yang Efektif untuk Meningkatkan Penjualan di Funn Maumere - Emilianus Eo Kutu Goo; Sahrul Hidayat; Nelci Elvida Klega; Asdianti Asdianti; Yusliani Julein Wole; Afdal Sayhudin (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
This community service activity aims to strengthen the marketing strategy of FUNN Maumere as a culinary business operating in an increasingly competitive market environment. The program was conducted using a qualitative descriptive approach through field observations, interviews with business owners and employees, and direct mentoring in implementing more effective marketing strategies. The results indicate that FUNN Maumere has applied a combination of traditional and digital marketing strategies, including brochure distribution and active promotion through social media platforms such as Instagram, TikTok, and Facebook. The mentoring activities focused on optimizing digital marketing, improving service quality, and strengthening brand consistency. These efforts contributed positively to increased brand awareness, customer interest, and wider promotional reach. However, sales performance remains fluctuative due to external factors, such as weather conditions and differences in outlet location characteristics. Therefore, this community service emphasizes the importance of continuous product innovation, enhancement of customer experience, and optimization of digital marketing strategies to reduce dependency on external conditions. This activity is expected to serve as a practical reference and mentoring model for other culinary MSMEs in developing adaptive, innovative, and sustainable marketing strategies to improve competitiveness and business continuity.